Pengaruh Terpaan Trailer Film Joker Terhadap Keputusan Remaja Untuk Menonton Film Joker Di Bioskop - Savarino, Jocelyn Williams; Pradipta, Ade Devia; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2020)
ABSTRACT   The success of Joker film's gross income about $ 1,073,151,773 cannot be separated from the effort by the production house Warner Bross Pictures to promotes joker film by giving a trailer view on all kind of media platform including social media and some conventional media. The goal of this research is to find about how Joker's trailers affect the teenager's decision to watching the "Joker" movie in the cinema. This research uses quantitative explanatory methods with the Stimulus Organism Response theory. For the data analysis technique, this research uses a simple linear regression analysis with  SPSS 18 program. The result from this research showed us that the “Joker” trailer exposure could affect the teenager’s decision for watching the “Joker” movie in the cinema.   Keywords: Joker’s Film Trailer, Teenager’s Decision, Watching The “Joker” Movie In The Cinema, Stimulus Organism Response Theory